Flash Card Palindrome (FCPM): Critical Thinking Skills Stimulation Media to Support Early Childhood Education Curriculum in the Globalization Era - Sri Indriani Harianja; Winda Sherly Utami; Nyimas Muazzomi; Kasmiati (Jurnal Pedagogi dan Pembelajaran, 2025)
Early childhood often experiences difficulties in developing critical thinking skills due to the lack of engaging, contextual learning media that meet the curriculum demands in the globalization era. The unavailability of innovative stimulation media such as Flash Card Palindrome (FCPM) results in the learning process being less able to optimize children's cognitive potential in recognizing patterns, analyzing information, and solving simple problems. This study aims to determine the effectiveness of flash card palindrome (FCPM) media in improving critical thinking skills in children aged 5–6 years. The study employed a quantitative approach, utilizing a quasi-experimental method with an equivalent time series design, involving a sample of 13 children. Data were obtained through observation and analyzed using the Wilcoxon Signed-Rank Test because the data did not meet the assumption of normal distribution. The results showed a significant difference in critical thinking skills between posttest 1 and posttest 5 after treatment using FCPM. In conclusion, the use of Flash Card Palindrome (FCPM) has been proven to provide adequate stimulation for the development of critical thinking skills in early childhood through engaging, interactive, and developmentally appropriate activities. The implications of this research suggest that the use of innovative learning media, such as FCPM, can be an effective alternative strategy for PAUD teachers to stimulate critical thinking skills in young children and encourage the creation of enjoyable and meaningful learning experiences.